Operational experiences of a geothermal heat pump system - Török, Imre (Acta Agraria Debreceniensis, 2014)
Energy consumption nearly 40% operation translates of the buildings in Hungary. In the last 5–8 years we can see a breakthrough in the field of low energy buildings, increasing the demand for buildings ’energy efficient’, and realized several successful investments in our country. Nowadays thanks to the application system the number of public buildings increased environmental energy recovery system has been growing such as solar power, heat pumps.